2020
DOI: 10.1109/tpami.2018.2883941
|View full text |Cite
|
Sign up to set email alerts
|

ADMM-CSNet: A Deep Learning Approach for Image Compressive Sensing

Abstract: Compressive sensing (CS) is an effective approach for fast Magnetic Resonance Imaging (MRI). It aims at reconstructing MR images from a small number of under-sampled data in k-space, and accelerating the data acquisition in MRI. To improve the current MRI system in reconstruction accuracy and speed, in this paper, we propose two novel deep architectures, dubbed ADMM-Nets in basic and generalized versions. ADMM-Nets are defined over data flow graphs, which are derived from the iterative procedures in Alternatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
440
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 695 publications
(442 citation statements)
references
References 84 publications
1
440
0
1
Order By: Relevance
“…This aliasing artifact‐based approach showed smaller errors than the CS algorithms . Also, a learning‐based approach was applied to unfold sparse recovery framework and outperformed CS algorithms …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This aliasing artifact‐based approach showed smaller errors than the CS algorithms . Also, a learning‐based approach was applied to unfold sparse recovery framework and outperformed CS algorithms …”
Section: Introductionmentioning
confidence: 97%
“…In recent studies, deep learning algorithms, especially convolutional neural networks (CNNs), have been applied to reconstruct MR images from the incoherently down‐sampled data or to produce 7T‐like high resolution (HR) images from 3T MR images . Bahrami et al.…”
Section: Introductionmentioning
confidence: 99%
“…We iteratively (or alternately) applied 2 different CNNs operating on different domains (the k‐space and image domain), and data consistency was interleaved among the CNNs. The second limitation of the earlier studies is that the network depth was shallower (3 to 5 layers) than that of most networks used in recent image‐restoration studies . In some studies, deep CNNs with layer depths greater than 20 afford much more promising results than shallower networks because of their larger receptive fields .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, several recent studies have demonstrated the applicability of deep‐learning techniques to the reconstruction of undersampled MR images or CT images . In training, tuples of undersampled images and fully sampled images are fed to convolutional neural networks (CNNs) to learn the relationship between the undersampled images and the corresponding fully sampled images .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation